Real-time implementation of a robust simplified intelligent proportional–integral control for CubeSat attitude determination system. (May 2020) - Gaber, Khaled; El_Mashade, Mohamed B.; Aziz, Ghada A. Abdel
Abstract: This paper presents a real-time implementation of a novel simplified intelligent (SI PI) control for a low-cost attitude determination and control system (ADCS) for CubeSat. As small satellite missions are increasing, the CubeSat requires precise ADCS with attitude drift adjustment. This attitude drift if not properly compensated, the attitude knowledge will be lost as the error will increase between the actual and estimated attitudes. The proposed ADCS comprises two steps; the attitude determination which estimates the current CubeSat's attitude and a novel simplified intelligent proportional-integral (SI PI) control algorithm that accurately adjusts the attitude. The control algorithm has no controller gains parameters and is based on the multi degree-of-freedom concept. To correct the attitude drift, the proposed ADCS utilizes magnetometer, sun sensor, and a micro-electro-mechanical (MEMS) gyroscope sensor which offers a comparative attitude that is utilized to update the estimated attitude delivered to the Kalman filter to determine the CubeSat's angular velocity and attitude. ADCS model validation and verification are performed via MATLAB R2019b and hardware implementation. Comparison with other ADCS techniques is presented. ADCS simulated model proves precision results with error no more than 0.1 degree.